Candidatus Syntrophosphaera thermopropionivorans: a novel player in syntrophic propionate oxidation during anaerobic digestion. Issue 4 (26th April 2019) - Dyksma, Stefan; Gallert, Claudia
Summary: Propionate is an important intermediate in the anaerobic mineralization of organic matter. In methanogenic environments, its degradation relies on syntrophic associations between syntrophic propionate‐oxidizing bacteria (SPOB) and Archaea . However, only 10 isolated species have been identified as SPOB so far. We report syntrophic propionate oxidation in thermophilic enrichments of Candidatus Syntrophosphaera thermopropionivorans, a novel representative of the candidate phylum Cloacimonetes . In enrichment culture, methane was produced from propionate, while Ca . S. thermopropionivorans contributed 63% to total bacterial cells. The draft genome of Ca . S. thermopropionivorans encodes genes for propionate oxidation via methymalonyl‐CoA. Phylogenetically, Ca . S. thermopropionivorans affiliates with the uncultured Cloacimonadaceae W5 and is more distantly related (86.4% 16S rRNA gene identity) to Ca . Cloacimonas acidaminovorans. Although Ca . S. thermopropionivorans was enriched from a thermophilic biogas reactor, Ca . Syntrophosphaera was in particular associated with mesophilic anaerobic digestion systems. 16S rRNA gene amplicon sequencng and a novel genus‐specific quantitative PCR assay consistently identified Ca . Syntrophosphaera/ Cloacimonadaceae W5 in 9 of 12 tested full‐scale biogas reactors thereby outnumbering other SPOB such as Pelotomaculum, Smithella and Syntrophobacter . Taken together the ubiquity and abundance of Ca . Syntrophosphaera, those SPOB might be key players for syntrophic propionate metabolism that have been overlooked before.